Un Plan de Cuentas Social y Ambiental No Financiero y los Principios del Pacto Global de Naciones Unidas (2021)
International initiatives of recognized importance have made proposals for the preparation and issuance, by economic organizations, of reports on economic, financial, social and environmental aspects for a more sustainable development and the UN Global Compact transcends various initiatives. Research and developments on a considered social and environmental accounting specialty with a socio-environmental approach, complementary to the economic-financial one are rescued. In this article, the specific objective is to complete a chart of accounts with a non-financial socio-environmental approach for the Sustainable Development Goals, considering the Principles of the United Nations Global Compact. Inductive and deductive analyses are carried out, comparing the constituted with the constituent, triangulating with sustainability reports, and completing a chart of accounts with aspects of the Global Compact. It is inferred that it is possible to complete a basic and flexible chart of accounts, with a non-financial socio-environmental approach for the Sustainable Development Goals, based on the Principles of the United Nations Global Compact.